The wandering lyrical subject in the poem A liberdade de seguir por esta via, by Eucanaa Ferraz - Luz, Daniel Rodrigues da [UNESP]; Borsato, Fabiane Renata [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2023)
Eucanaa Ferraz is a poet whose work crosses different thematic paths in the scenario of contemporary Brazilian literature. The work Escuta, released in 2015, presents strong traces of his artistic repertoire. From the mapping of the intertextual references of the work, this paper analyzes the poem entitled A Liberdade de Seguir por esta via, to show how the play Hamlet by William Shakespeare is taken up by the author; how it verifies the traits of the dramatic genre that appear in the poem, and the poem's relationship with the aesthetic proposal of the work, all from the perspective of a lyrical subject in displacement that expresses reflections on the landscape that he accompanies during a trip. The work is based on Anatol Rosenfeld's studies on the theory of genres, as well as texts on theatrical aesthetics and criticism of the author's work.
Keywords: Anatol Rosenfeld; Eucanaa Ferraz; Hamlet; Brazilian contemporary poetry; lyrical subject